THE RULES OF IJTIHAD AND ITS URGENCY IN ISLAMIC JUSTICE IN INDONESIA (An Analysis of The Book al-Qawā’id al-fiqhiyyah bayna al-aṣālah wa al-tawjīh by muhammad bakr ismail) - Ayus Permana; Muhammad Fikri Adrian; Asmuni Asmuni (JURNAL HAKAM, 2025)
This research discusses the rules of fiqh related to ijtihad in the context of Islamic justice, with reference to the paper entitled al-Qawāʿid al-Fiqhiyyah Bayna al-Aṣālah wa al-Tawjīh by Muhammad Bakr Ismail. Rules of Fiqh are a basic principle in Islamic law that serves as a methodological guideline in understanding and applying law contextually. In judicial practice, ijtihad plays an important role in resolving cases that are not explicitly regulated in the nash, including in the process of evaluating evidence and making legal decisions. This study uses a literature study method with a descriptive-analytical approach to identify and analyze the relevance of fiqh principles to the ijtihad process in Islamic courts.The results of the study show that principles such as al-ijtihādu lā yunqadhu bi al-ijtihād, al-tarjīḥ lā yaqa’u bikasrat al-’ilal, lā ḥujjata ma’a al-iḥtimāl al-nāshi’ ‘an dalīl, al-waṣfu fī al-ḥāḍir laghwun wa fī al-ghā’ib mu’tabar, and al-ṣulḥu jā’izun bayna al-muslimīn illā ṣulḥan ḥarrama ḥalālan aw aḥalla ḥarāman play a role in maintaining objectivity, rigor, and fairness in decision-making. Thus, a deep understanding of the rules of fiqh becomes an important foundation in directing the practice of ijtihad that is not only valid according to sharia, but also relevant to the dynamics of the law and the need for justice in contemporary society.